EFFECT OF WATERING FREQUENCY ON FEED INTAKE, MILK PRODUCTION ANDCOMPOSITION IN SAHIWAL CATTLE DURING SUMMER - A. Ali; M. I. Mustafa; M. Q. Bilal; G. Muhammad; M. Lateef; S. Ullah (Journal of Animal and Plant Sciences, 2015)
The study was carried out to investigate the effect of watering frequency on feed intake, milk production and composition in Sahiwal cattle during summer at the Livestock Experiment Station, University of Agriculture, Faisalabad. Twelve cows, almost at same number and stage of lactation were selected, and divided into three groups viz. G-1. G-2 and G-3 in a completely randomized design. Three Treatments including: watering twice a day, watering thrice a day and ad libitum watering were allocated to these groups. Animals were housed individually for individual watering and feeding. Green fodder was offered ad libitum to cows of all treatment groups and concentrate was offered 2.0 kg per cow per day as a production allowance. Results showed that watering frequency had a significant (P<0.001) effect on water intake, dry matter intake, milk production and digestibility. The water intake in cows of group G-1, G-2 and G-3 was 37.09, 40.20 and 40.68 liters, respectively. Dry matter intake in cows of group G-1, G-2 and G-3 was 9.90, 10.60 and 10.67 kg, respectively. Milk production in G-1, G-2 and G-3 was 6.41, 7.52 and 7.46 liters, respectively. Digestibility of feed in cows of group-G1, group-G2 and group-G3 was 73.37%, 66.08% and 69.74%, respectively. Watering frequency had a significant effect (P<0.001) on water intake, dry matter intake, digestibility percentage and milk production. The watering frequency however, showed non-significant effect on milk composition in all treatment groups.
Keywords: watering frequency; feed intake; milk; dairy cows